B2B in the ceramics industry : perspectives for an internet based platform - Maggioli, Elio Majoli; Johri, Lalit M.; Bechter, Clemens; Tocquer, Gerard A. (Pathum Thani, Thailand : Asian Institute of Technology, 2001)
The hottest topic ll1 B2B today is e-markets. All over the world executives are asking themselves, "Which digital market software platform should we buy or espouse?" and "Which e-procurernent vendor will gain the most momentum?" This paper analyses the opportunity, from a Ceramics Machinery manufacturer perspective, to extend the range of its activities by building a vertical business platform and Application Service Provider ("ASP") providing business-to-business solutions for the global ceramics industry. F or the ceramics machinery manufacturer, the 31m is to conceive, market, and enrich an online system that delivers real business value for the ceramics industry operators, and to couple this system with the bricks and mortar activities it performs at manufacturing level. Relying on its expertise and understanding of the ceramics industry value chain, the corporation's ultimate goal is to create an its own distinctive competitive advantage, which will eventually bring about increased global market penetration and higher profits.
A research study submitted in partial fulfillment of the requirements for the degree of Master in Business Administration (Executive MBA Program)
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2001
Keywords: Industrial marketing -- Computer network resources; Business -- Marketing; Application service providers; Electronic commerce -- Computer networks